Rosalie Nichols, Wiggsy Sivertsen, Johnie Staggs - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows, from left to right, Rosalie "Nikki" Nichols, Wiggsy Sivertsen, and Johnie Staggs at an event with other people milling around behind them. Wiggsy has a corsage and a name tag attached to her sweater. The name tag reads: "Hi [my name is?] Wiggsy Sivertsen". The other two women are wearing stickers, possibly name tags, with a symbol on it.